Two thirds of species in a global shark fin trade hub are threatened with extinction: Conservation potential of international trade regulations for coastal sharks - Cardeñosa, Diego; Shea, Stanley K.; Zhang, Huarong; Fischer, Gunter A.; Simpfendorfer, Colin A.; Chapman, Demian D. (Conservation letters, 2022)
One third of chondrichthyan species (sharks, rays, and chimeras) are threatened with extinction, mainly due to unsustainable fishing. Large accessible international markets for meat and luxury products like dried fins can help drive overfishing by encouraging targeted capture or retention of high‐value export species. If this is common, then species in international trade could have heightened extinction risk. Here, we examined the species composition of the Hong Kong shark fin market from 2014 to 2018, finding that traded species disproportionately occur in threatened categories (70.9%) and all premium value species are threatened. A small number of cosmopolitan species dominate the trade, but noncosmopolitan coastal species are still traded at concerning levels given their limited distribution. These coastal species are not generally subject to retention prohibitions, fisheries management, or international trade regulations and without management many could become extinct. The conservation potential of international trade regulations alone for coastal chondrichthyans depends on the extent to which overfishing is driven by export markets; socioeconomic studies of coastal fishing communities are needed to make this determination. Nonetheless, adding international trade regulations for more coastal shark species that are in the fin trade could prompt broad engagement with overfishing in nations lacking effective management.